Pembangunan Wilayah Secara Berimbang - Kuswandi, Aos (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2012)
The ideal region development is the balance inter regional development. Disparity of region development in Indonesia has been in pathetic condition both in the balance between rural and urban area and inter regional of the west, middle, and east of Indonesia area as well. One of the efforts that can be done is from the development planning process both in sectoral and development area. The prudence in planning is preventive action to produce the exact output policy.